Odciski tkaniny płóciennej na naczyniu z Poznania Nowego Miasta (stan. 362) - Sikorski, Andrzej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The paper discusses cloth impressions on the surface of early medieval pottery shards from site 362, Poznań Nowe-Miasto. The cloth was possibly made from flax and used a plain weave. Owing to the good preparation of yarn, a high quality product was obtained. It was wrapped around a potter’s tool, probably made of wood and used for smoothing out the outer surface of a 7th-8th-century vessel.